Primary Capreomycin Resistance Is Common and Associated With Early Mortality in Patients With Extensively Drug-Resistant Tuberculosis in KwaZulu-Natal, South Africa. (15th August 2015) - O'Donnell, Max R.; Pillay, Melendhran; Pillay, Manormoney; Werner, Lise; Master, Iqbal; Wolf, Allison; Mathema, Barun; Coovadia, Yacoob M.; Mlisana, Koleka; Horsburgh, Charles Robert; Padayatchi, Nesri
Abstract : Background: Capreomycin is a key antimycobacterial drug in treatment of extensively drug-resistant tuberculosis (XDR-TB). Drug-susceptibility testing (DST) for capreomycin is not routinely performed in newly diagnosed XDR-TB in South Africa. We performed this study to assess the prevalence, clinical significance, and molecular epidemiology of capreomycin resistance in newly diagnosed patients with XDR-TB in KwaZulu-Natal, South Africa. Methods: Retrospective cohort study of consecutive patients with XDR-TB admitted to a TB referral hospital without previous XDR-TB treatment. A subset of isolates had extended DST (including capreomycin), mutational analysis, and IS6110 restriction fragment length polymorphism assays. Results: A total of 216 eligible patients with XDR-TB were identified. The majority were treated with capreomycin (72%), were young (median age: 35.5 years), and were female (56%). One hundred five (76%) were HIV+, and 109 (66%) were on antiretroviral therapy. A subset of 52 patients had full DST. A total of 47/52 (90.4%) patients with XDR-TB were capreomycin resistant. Capreomycin-resistant patients experienced worse mortality and culture conversion than capreomycin susceptible, although this difference was not statistically significant. The A1401G mutation in the rrs gene was associated with capreomycin resistance. The majority of capreomycin-resistant strains were F15/LAM4/KZN lineage (80%), and clustering was common in these isolates (92.5%). Conclusions: Capreomycin resistance is common in patients with XDR-TB in KwaZulu-Natal, is predominantly because of ongoing province-wide transmission of a highly resistant strain, and is associated with high mortality. Capreomycin should be included in routine DST in all patients with XDR-TB. New drug regimens that do not include injectable agents should be operationally tested as empiric treatment in XDR-TB. Abstract : Supplemental Digital Content is Available in the Text.